Project Management for Instructional Designers - Clements, Geri; Drysdale, Jeffery; Francis, Jenifer (Open textbook library., 2012)
Project Management for Instructional Designers (PM4ID) is – as the name suggests – a book about project management tailored specifically for instructional designers. This book is a revise / remix of a pre-existing, openly licensed project management textbook which was donated to the commons by a benefactor that desires to be attributed as Anonymous. PM4ID includes many new features and improvements to the original book, including: Alignment of book chapters with the PMBOK, which supports readers in preparing for the Project Management Professional certification, A series of video cases of project managers working in the instructional design area, integrated into every chapter, Multiple versions of the book, including HTML, PDF, ePub, Kindle, and a text-to-speech mp3 audio version of the book, New examples written specifically for readers coming from the instructional design perspective, and more.